Ethics of Leadership in Sivagama Text - Ida Bagus Putu Suamba (Pusat Kajian Bali Universitas Udayana, 2020)
Ethics of leadership has been dominated by western views about ruling a country; hence marginalizing local cultural ethics of leadership in practice. This paper explores the ethics of leadership as contained in the Balinese text ?iv?gama composed by Ida Pedanda Madé Sidêmên (1858–1984) and its relevance for the modern era. Data was taken from lontar palm-leaf manuscripts and analyzed in a qualitative way focusing on the conception of nava natya (nine ethical principles) of leadership. Also included was the pañca visaya, five external objects and the corresponding senses, which can cause harm when facing enemies. In the past, these ethical principles were used as the basis upon which the royal system of governance was practiced for the welfare of all. This concept is still relevant nowadays as long as service is considered to be a human virtue. The research results thus offer a contribution to the study of leadership ethics in the Old Javanese tradition.